KHM Yunus Martan Leadership Type in the Development of Pesasntren As'adiyah - Ahmad Muktamar B (Jurnal Mantik, 2022)
ABSTRACT This study describes the charismatic leadership type of the kyai by focusing on the leadership type of K.H.M. Yunus Martan in the development of the Pesantren As'adiyah Sengkang. Aims to review the personal identity, work and leadership type of K.H.M. Yunus Martan in developing the Pesantren As'adiyah. This study uses a qualitative descriptive approach which is carried out by compiling and describing the life and type of leadership of K.H.M. Yunus Martan in developing the Pesantren As'adiyah. Data was collected by means of observation, interviews, literature studies and documents related to the researched. After the data was collected, a descriptive qualitative analysis was carried out in the form of a narrative. The results of this study indicate that the individualistic and centralistic characteristics of the charismatic leadership type of kyai in pesantren, do not fully apply to the leadership of K.H.M. Yunus Martan. In the management of the Pesantren As'adiyah, K.H.M. Yunus Martan actually involved the management and all elements of As'adiyah. Likewise, the decision-making process is carried out through deliberation and meetings. Both of these are characteristics of the democratic type of leadership. This study also found that K.H.M. Yunus Martan is a person with makarame leadership behavior. It is based on personal qualities characterized by his extraordinary firmness and discipline in all aspects of his activities. Firmness and discipline are the keys to his success in developing Pesantren As'adiyah. Keywords: leadership type, leadership in pesantren, charismatic, makarame